Communication and Health In Drug Addict Rehabilitation: Criminal Instruments To Health Law Services - Ani Purwati; Gita Ruslita (International Journal Of Community Service, 2026)
Drug abuse in Indonesia should no longer be viewed solely as a criminal issue, but also as a health, social, psychological and humanitarian problem requiring comprehensive treatment. This community service activity aimed to improve public understanding regarding rehabilitation as a health-based approach for drug addicts and to strengthen awareness of restorative justice and social reintegration. The activity was conducted at Wisma Bhisma YAKITA, Ciawi Bogor, on May 23, 2026, involving drug addicts undergoing rehabilitation, former addicts in recovery, families, healthcare workers, counsellors, academics, students, and community members. The program applied a participatory educational method integrating health communication and health law approaches. The materials included rehabilitation law, restorative justice, therapeutic communication, community-based recovery, aftercare, and the 12 Steps Recovery Program. The implementation methods consisted of interactive lectures, group discussions, motivational counselling, psychosocial approaches, experience sharing, and case-based presentations. The results showed that participants initially viewed rehabilitation mainly as an alternative punishment rather than a comprehensive recovery process. After the program, participants demonstrated improved understanding regarding addiction as a chronic health condition requiring long-term recovery, empathetic communication, family support, and sustainable aftercare. The activity also highlighted the importance of multidisciplinary collaboration among families, healthcare workers, rehabilitation institutions, communities, and law enforcement agencies in creating a humane and justice-oriented rehabilitation system.